Clinical and epidemiological features of textile contact dermatitis:an Italian multicentre study. (7th January 2014) - Lisi, Paolo; Stingeni, Luca; Cristaudo, Antonio; Foti, Caterina; Pigatto, Paolo; Gola, Massimo; Schena, Donatella; Corazza, Monica; Bianchi, Leonardo
Summary Background The prevalence of occupational and non‐occupational textile dermatitis seems to be increasing, probably because of changed textile manufacturing techniques. Objective Evaluation of the clinical features and epidemiology of textile contact dermatitis (TCD) in Italy. Methods Demographic data, clinical history aspects, atopy and positive patch test reactions to occupational and non‐occupational allergens were investigated in 277 textile dermatitis patients. Results Contact dermatitis was the most frequent clinical presentation (95.3%). TCD was more common in females, in the fourth to fifth decades of life, and in atopic dermatitis patients. The lesions were prevalently eczematous (74.2%), and mostly located on the trunk and lower limbs in non‐occupational cases, and on the hands in textile workers. Allergic TCD (58.3%) was more frequent than irritant TCD. The dyes (Disperse Blue 124, Disperse Blue 106, and Disperse Yellow 3) were most frequently responsible (79.8%), especially in non‐occupational TCD. Formaldehyde and resins were more important in occupational TCD. Concomitant reactions among textile dyes and/or finishing resins were observed in 50.0% of patients. Conclusions Some strategies (sensitization potential of new textile chemicals, more stable dyes, reduced levels of formaldehyde in clothing, and collaboration with textile industry and trade associations) should be adopted to decrease the TCD incidence and update the textile patch testing series.